2006
DOI: 10.1016/j.ydbio.2006.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the initial follicle pool: Empirical and mathematical evidence supporting its sufficiency for adult fertility

Abstract: The importance of the initial follicle pool in fertility in female adult mammals has recently been debated. Utilizing a mathematical model of the dynamics of follicle progression (primordial to primary to secondary), we examined whether the initial follicle pool is sufficient for adult fertility through reproductive senescence in CD1 mice. Follicles in each stage were counted from postnatal day 6 through 12 months and data were fit to a series of first-order differential equations representing two mechanisms: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
109
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 15 publications
7
109
0
1
Order By: Relevance
“…In contrast to these reports, other recent reports have provided evidence that adult oogenesis and the so-called GSCs do not exist and have questioned the above-mentioned findings (8)(9)(10)(11)(12). For example, by tracing the proliferation of cultured Ddx4-positive cells in vitro, a recent study from our group reported that no mitotically active GSCs exist in the postnatal mouse ovary (10).…”
mentioning
confidence: 73%
“…In contrast to these reports, other recent reports have provided evidence that adult oogenesis and the so-called GSCs do not exist and have questioned the above-mentioned findings (8)(9)(10)(11)(12). For example, by tracing the proliferation of cultured Ddx4-positive cells in vitro, a recent study from our group reported that no mitotically active GSCs exist in the postnatal mouse ovary (10).…”
mentioning
confidence: 73%
“…The dynamics of the follicle population were simulated according to two distinct models: a fixed pool model and a stem cell model in the mouse ovary. The fixed pool model accurately reflected the experimental decrease in follicle numbers and allowed the authors to refute the concept of GSC replenishment in the adult ovary [18] . Johnson's assumption that busulfan was only toxic to GSCs and does not kill primordial follicles was questioned by two groups [16,17] .…”
Section: Existence Of Ovarian Gscsmentioning
confidence: 90%
“…Following the publication of this landmark article, Johnson et al [1] were confronted by criticism and skepticism [16][17][18][19][20] . The main criticisms were related to the subjectivity of the scoring, the tissue fixation protocol, the mathematical model used to calculate the follicular dynamics, the toxicity of busulfan to follicles, the capacity of BrdU-MVH-double-positive cells for oocyte Ozakpinar OB et al .…”
Section: Existence Of Ovarian Gscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical data is scarce for primordial follicles [46], is calculated by inference for primary follicles [30], and simply does not exist for secondary follicles [19]. As a direct result of these limitations, two entirely different and contradictory compartmental models have been published in the literature [6,18]. A third research group investigating the same cell dynamics but with its own empirical data and modelling assumptions would be highly likely to produce a third quantitative model being fundamentally different to those already published.…”
Section: Quantitative Mathematical Modelsmentioning
confidence: 99%